2018
DOI: 10.1149/2.0351811jes
|View full text |Cite
|
Sign up to set email alerts
|

The Properties of Carbons Derived through the Electrolytic Reduction of Molten Carbonates under Varied Conditions: Part I. A Study Based on Step Potential Electrochemical Spectroscopy

Abstract: Carbons have been produced through the electrolytic reduction of molten alkali metal carbonate salts under a range of conditions. The resultant carbons consist of both graphitized and amorphous phases. The carbon surface has also been shown to be heavily functionalized with oxygen containing groups. Their charge storage capabilities as electrochemical capacitor materials have been investigated using cyclic voltammetry and step potential electrochemical spectroscopy (SPECS). Trends in carbon performance with el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
40
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(52 citation statements)
references
References 59 publications
11
40
1
Order By: Relevance
“…Phases of this form have been stated to correspond to graphitic carbon by previous groups . These phases are apparently present in low concentrations and are slightly more prevalent towards the edges of particles, which is consistent with what is expected in carbons electrodeposited at low temperatures and current densities based on previous results . The observable concentration of graphitic phases in these carbons is lower than that which has been observed in previously synthesized carbons in molten carbonate systems, which is likely due to the manner of synthesis being chosen to produce carbon with increased amorphous character.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Phases of this form have been stated to correspond to graphitic carbon by previous groups . These phases are apparently present in low concentrations and are slightly more prevalent towards the edges of particles, which is consistent with what is expected in carbons electrodeposited at low temperatures and current densities based on previous results . The observable concentration of graphitic phases in these carbons is lower than that which has been observed in previously synthesized carbons in molten carbonate systems, which is likely due to the manner of synthesis being chosen to produce carbon with increased amorphous character.…”
Section: Resultssupporting
confidence: 90%
“…[31,39,42,43] The research presented here continues from the work of this group, [27,28] which has shown how temperature, current density, substrate, and electrolyte variation influences the morphology of carbonate derived carbons, and how these morphological changes relate to aqueous supercapacitive performance in the materials. [27,28] This has indicated that electrochemical performance in aqueous systems is at its highest for materials showing elevated amorphous character, which contributes to increased double layer formation, [28] and high oxygen functionalization, which leads to high pseudo-capacitance. [28] These carbons may be produced through the electroreduction of molten carbonates at low temperatures [23][24][25]28,[29][30][31] or at low current densities relative to the geometric surface area of the working electrode.…”
mentioning
confidence: 90%
See 3 more Smart Citations